Flood Vulnerability Using Multi-Criteria Analysis in West Jakarta - Muhamad Ikhsan; Purnama Budi Santosa (Politeknik Negeri Batam, 2025)
The Special Capital Region of Jakarta, located on the north coast of Java Island, is a low-lying sedimentary area crossed by 13 rivers, making it highly vulnerable to flooding from river overflows and sea level rise intensified by climate change. Flooding has been a persistent issue since the Dutch colonial era, driven by rapid urban growth, inadequate development management, the emergence of slums, and poor water resource management. Major floods occurred in 2002 and 2007, and annual floods continued until 2020. Several key factors contribute to flooding, including slope, rainfall, and land cover, while in West Jakarta the problem is further exacerbated by land subsidence and sea level rise. To address this, a flood vulnerability analysis was carried out using a GIS-based multi-criteria analysis approach. Unlike the BNPB reference, which considers only slope, rainfall, and land cover, this study incorporated six parameters: land cover, rainfall, drainage density, slope, land subsidence, and sea level rise. Each parameter was weighted based on its contribution to flooding risk, and spatial data were processed through overlay and reclassification to produce a flood vulnerability map. The results categorize West Jakarta into four classes: Not Vulnerable, Slightly Vulnerable, Vulnerable, and Highly Vulnerable. The majority of the area falls into Not Vulnerable (39.62%) and Slightly Vulnerable (36.30%), while only Kembangan District is dominated by the Highly Vulnerable category. Validation was conducted by comparing the vulnerability map with historical flood data from 2016 to 2023. The comparison shows a strong positive correlation between mapped vulnerability levels and the frequency of actual flood events. This alignment confirms the validity of the method and highlights its value for improving flood risk management and mitigation planning in West Jakarta.